Efektifitas Penerapan Cooperative Scrift Dalam Meningkatkan Kemampuan Memahami Bacaan Siswa Kelas V Sd Negeri 17 Parepare - Abdul Halik; Muhamad Asrul Sultan; Zaid Zainal (Prodi PGSD FIP UNM, 2017)
In Indonesian language learning In Primary School there are four skills that need to be mastered by the students that is listening skill, writing skill, reading skill, and speaking skill. In reading learning, students often feel bored and unmotivated in learning. Related to the importance of learning read comprehension, necessary methods that can foster motivation and interest of students in reading comprehension activities in school. Learning comprehension reading should be done with appropriate learning methods to achieve optimal learning outcomes. This study aims to examine the effectiveness of Cooperative Script method, in improving reading comprehension in grade V students of SD Negeri 17 Parepare. The type of this research is experimental research using one group pretest posttest design. Variables in this research is Cooperative Script Method as independent variable and skill reading comprehension level as dependent variable. The sample in this study is all students of class V SD Negeri 17 Parepare which amounted to 37 people. Technique of collecting data using comprehension reading comprehension test in the form of objective test 30 item. The validity of the instrument used is the content validity. Reliability test was analyzed by using alpha cronbach coefficient formula. Data analysis technique is done by using t-test technique with respect to normality and homogeneity. The results showed that the mean score of students' reading ability before and after treatment increased from 16.86 to 24.06. The result of t-test analysis shows t-test equal to -24,829 with db = 36, and p value 0.000. The p value is smaller than the significance level of 0.05. In other words, the Cooperative Script method is effectively used in reading comprehension learning.